Development of Internet of Things Optical Sensor based on Surface Plasmon Resonance Phase Interferometry - Hock Kin, Tan; Arsad, Norhana; Hadri Hafiz Mokhtar, Mohd; Saiful Dzulkefly Zan, Mohd; Hidayah Azeman, Nur; Ashrif A Bakar, Ahmad (International Journal of Engineering and Technology, 2019)
This paper demonstrates the integration between an Internet of Things platform and an optical sensor based on surface plasmon resonance (SPR) phase interferometry. The optical sensing system starts when the liquid containing the heavy metal is flowing through the top surface of a glass prism.Â  A laser is turned on and a motor can sweep from 0 to 90 degrees initially. Data is collected by a photodiode sensor. The SPR angle is determined where the reflectivity of light falls to the minimum level. The motor rotation is then fixed at the SPR angle. Self-mixing interferometry is applied by reflecting back the light from laser using a piezo actuator. The resulting phase difference is measured, and the concentration of heavy metal can be determined using virtual instrument (VI). VI consists of control of the optical sensing system which is built in LabVIEW software and installed in a host computer. A web page is created based on the VI using Web Publishing Tool which allows user to monitor the data collected from the optical sensor by entering the URL address in the Internet Explorer from the client computer. Keysight BenchVue software is used to monitor and control the function of oscilloscope. The result of this project is an optical sensor capable of sensing different concentration of heavy metals in which the real-time data collected from it can be monitored remotely using computer and smartphone.Â Â